Evaluasi Penerapan Akuntansi Untuk Kontrak Asuransi Pada PT Asuransi AXA Indonesia - Amrie Firmansyah; Elisabeth Octa Cesara (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
This study aims to analyze the application of financial accounting standards namely PSAK 62 (2015) regarding insurance contracts and PSAK 28 (2012) regarding loss insurance accounting at PT Asuransi AXA Indonesia, considering that PT Asuransi AXA Indonesia only provides services in the field of loss insurance excluding life insurance. This study uses qualitative methods with content analysis. The data used in this study is sourced from the official website of the relevant company, the data used as a sample are the financial statements of PT Asuransi AXA Indonesia from 2011 up to 2017. The analysis of this research was conducted on the presentation and disclosure of the company's financial statements adjusted to the provisions of accounting standards and applicable regulations. The results of this study indicate that PT Asuransi AXA Indonesia has implemented the recognition, measurement and presentation of premium income, claims and acquisition costs applied by those in accordance with PSAK 28 (2012) as well as PSAK 62 (2015).